EFEKTIVITAS PROGRAM PEMANTAUAN JENTIK NYAMUK (PJN) SECARA MANDIRI DALAM PENANGGULANGAN KASUS DEMAM BERDARAH DENGUE (DBD) DI KELURAHAN KEDUNGMUNDU, KECAMATAN TEMBALANG, KOTA SEMARANG - Disayna Azzahra Yuniaz, Arla; Widowati, Nina; Maesaroh, Maesaroh (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2024)
The Independent Mosquito Larvae Monitoring Program (PJN) is one of the programs implemented by the Semarang City Government to address environmental problems and efforts to prevent and reduce the spread of Dengue Fever (DBD) through independent monitoring and eradication of mosquito nests in each household. Kedungmundu Village is an area that implements the Independent Mosquito Larvae Monitoring Program (PJN). The method used in this study is descriptive qualitative with interview data collection techniques, documentation and literature studies. The indicators used to determine the effectiveness of the program are the accuracy of the program's targets, program socialization, program objectives and program monitoring. In addition, the driving and inhibiting factors of the program are seen from environmental conditions, relationships between organizations, organizational resources for program implementation, and the characteristics and capabilities of implementing agents. The results of the study indicate that the Independent Mosquito Larvae Monitoring Program (PJN) cannot be said to be fully effective because there are still people who do not understand the intent and purpose of the program, improving environmental quality and community participation are not optimal and program monitoring has not provided real changes for the community. The inhibiting factors of the program come from environmental conditions, relationships between organizations, organizational resources, and the capabilities of program implementers. The author's suggestion to optimize the effectiveness of the program is the need to conduct intensive socialization using appropriate media for the community, strengthening cooperation between related parties and the community in developing the Independent Mosquito Larva Monitoring Program (PJN) to protect the environment and reduce the population of mosquitoes that cause high cases of Dengue Fever (DBD). Inhibiting factors of the program can be overcome through coordination and communication between stakeholders.